2(3x-7)+x=4-6x

Simple and best practice solution for 2(3x-7)+x=4-6x equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 2(3x-7)+x=4-6x equation:


Simplifying
2(3x + -7) + x = 4 + -6x

Reorder the terms:
2(-7 + 3x) + x = 4 + -6x
(-7 * 2 + 3x * 2) + x = 4 + -6x
(-14 + 6x) + x = 4 + -6x

Combine like terms: 6x + x = 7x
-14 + 7x = 4 + -6x

Solving
-14 + 7x = 4 + -6x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '6x' to each side of the equation.
-14 + 7x + 6x = 4 + -6x + 6x

Combine like terms: 7x + 6x = 13x
-14 + 13x = 4 + -6x + 6x

Combine like terms: -6x + 6x = 0
-14 + 13x = 4 + 0
-14 + 13x = 4

Add '14' to each side of the equation.
-14 + 14 + 13x = 4 + 14

Combine like terms: -14 + 14 = 0
0 + 13x = 4 + 14
13x = 4 + 14

Combine like terms: 4 + 14 = 18
13x = 18

Divide each side by '13'.
x = 1.384615385

Simplifying
x = 1.384615385

See similar equations:

| 80+9t=7t | | 6y-2(5+3y)=15 | | -6x-2(5x-5)=-118 | | 3m-15=-5 | | 0.4x-x=49 | | 1.5x-7=11-1.5x | | -x^3+2x^2+x-2=0 | | (2x+6)=42 | | (6x^3-6x^2+2x)+(8x^3+9x^2-13x)= | | -5+4(2x+13)=16 | | 24+1.50m=3m | | 18x^2+9xy-20y^2=0 | | -9y-12=8-4y | | 3x+4=6x-8 | | 4x+7(-x+4)=13 | | 8-(3n-1)=5-4n | | (2r+6)/5=-4 | | y^3-7y^2+3y-21=0 | | 8=30 | | 2x-10=4x+30 | | 3x+5-7(x+1)=4x+3 | | 7h-4=12-3h | | -64=4x-2(-5x-10) | | (m-2)/9=3 | | -5v-10=-110 | | 1+8e-2e=22 | | 3=-1.5n | | 16d^2-14d-15=0 | | 2(6-x)=2x+6 | | 4(x)+10=38 | | 21-4h-13=37+13h | | 2x-6=6x-18 |

Equations solver categories